Surveillance imaging and radiation exposure in the detection of relapsed neuroblastoma. Issue 10 (15th June 2016) - Owens, Cormac; Li, Bryan K.; Thomas, Karen E.; Irwin, Meredith S.
Abstract: Background: More than half of children with high‐risk neuroblastoma (NB) will experience recurrence. Radiologic imaging is used for initial staging and during therapy to assess response. However, the role of surveillance imaging in the detection of relapse has not been well studied. Surveillance potentially results in high cumulative exposure to ionizing radiation, which may be associated with an increased risk of developing second malignancies. Procedure: We reviewed NB cases at our institution between 2000 and 2011. We calculated radiation exposure due to imaging (during diagnosis, treatment, and posttherapy surveillance) using cumulative effective dose (CED) estimates and determined whether cross‐sectional imaging identified recurrences. Results: Fifty of 183 patients with NB experienced a recurrence. The median time from diagnosis to relapse was 1.20 years (range: 0.18–6.66 years). Most patients had evidence of metastases and only 4 of 50 patients presented with isolated primary tumor site recurrences. The mean CED prior to relapse was 125.2 mSv (range: 24.5–259.7), 64% of which was from computed tomography (CT) scans. Thirty‐seven of 50 patients had clinically evident or measurable disease detected by X‐ray (XR), ultrasound (US), or urinary catecholamines (UCats), and the addition of metaiodobenzylguanidine (MIBG) scans identified eight additional recurrences. Thus, cross‐sectional imaging (CT/MRI, where MRI is magnetic resonance imaging) was only required to identify 10% (5/50) of cases. Conclusion: Relapsed disease was detected in most patients by symptoms/exam, MIBG scan, UCats, and/or XR/US, supporting reduced use of CT imaging in posttherapy surveillance, thereby decreasing cumulative radiation dose. Refinement of surveillance imaging may be further guided by risk stratification, disease sites, and potentially biomolecular markers.